Driving Gigs in Oman: Women and Techno-Fixes in the Platform Economy - Crystal A. Ennis (Global Labour Journal)
Digital platforms mediating work between customers and service providers have expanded exponentially in the past decade, driving a growing research agenda on the impact of platform capitalism, AI and the gig economy on labour around the world. This paper is interested in understanding the platform economy at the intersection of gender with the political economy of labour. Focusing on the Omani case of a new women’s taxi service (OFemale) through the digital platform OTaxi, it asks how ride-hailing platforms are impacting women’s employment futures. Using rapid ethnography, elite interviews and a survey, the article examines both the launch and expansion of the business alongside the experiences of Omani women as taxi drivers. The article excavates three gendered discourses of freedom, protection and job creation around platform labour and female labour market participation in the region. It argues that digital platforms such as OTaxi offer techno-fixes to fill gaps in the market and respond to the need to generate job opportunities for female citizens in the country. At the same time, women make use of these opportunities and interpret their experience in diverse ways that problematise the neo-liberal promises of innovative technologies, job flexibility and autonomy embodied in platform capitalism.